167k views
3 votes
Hey guys

im new here
please solve this for me with steps!
ill mark as the best answer​

Hey guys im new here please solve this for me with steps! ill mark as the best answer-example-1
User Aashish
by
5.2k points

1 Answer

4 votes

Answer:

The factors of
2(x+y)^2-9(x+y)-5 is ((x+y)-5)(2x+2y+1)

Explanation:

Given polynomial

=>
2(x+y)^2-9(x+y)-5

To Find:

The factors of the polynomial =?

Solution:

Lets assume k = (x+y)

Then
2(x+y)^2-9(x+y)-5 can be written as
2k^2-9k-5

Now by using quadratic formula

k =
(-b\pm√((b^2-4ac))/(2a)

where

a= 2

b= -9

c= -5

Substituting the values, we get

k =
(-b\pm√((b^2-4ac)))/(2a)

k =
(-(-9) \pm √(((-9)^2-4(2)(-5)))/(2(2)))

k =
(-(-9) \pm √((81+40)))/(4)

k =
(-(-9) \pm √((121)))/(4)

k =
\frac{-(-9) \pm 11}}{4}

k=
( 9 \pm 11)/(4)

k =
(20)/(4) k =
(-2)/(4)


k_1 =5
k_2 = -(1)/(2)


2k^2-9k-5= 2(k-5)(k+(1)/(2))

Solving the RHS we get


(2)/(2)(k-5)(2k+1)


(k-5)(2k+1)

Substituting k = x+y


((x+y)-5)(2(x+y+1)


((x+y)-5)(2x+2y+1)

User Yakir Tsuberi
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.